Student´s Satisfaction with the Experiential Learning Hyflex: the case study of Ipam - Camejo, Maria João de Figueiredo e Salles (2021)
This study aims to assess which variables contribute the most to the undergraduate and master’s Students’ Satisfaction at IPAM Lisboa and IPAM Porto, regarding the new academic model adopted in these Higher Education Institutions - the Experiential Learning HyFlex. For this purpose, the Structural Equation Model proposed by Alves and Raposo (2007) was adapted, considering the constructs of Image, Expectations, Perceived Quality and Perceived Value, antecedents of Students’ Satisfaction. Data were collected through an online questionnaire using the SurveyMonkey platform, whose link was shared by e-mail with the 992 students eligible for the study. The validation and adjustment of the Alves & Raposo (2007) model were performed through a Confirmatory Factor Analysis, by means of the Maximum Likelihood statistical methodology, using the AMOS software (v. 27). The use of this software also allowed the analysis of direct and indirect effects between the constructs, performing the Bootstrap random resampling method. As far as outputs are concerned, it was found that all constructs have a positive and statistically relevant direct effect on the others, with exception of Expectations, which shows a negative and not statistically relevant direct effect on the constructs of Perceived Value and Students’ Satisfaction. At the end of the analysis, it was possible to conclude that the construct that most contributes, on a positive and statistically significant direct way, to Students’ Satisfaction with Experiential Learning HyFlex is Perceived Quality, i.e., the perception of quality that students have retained from the new academic model.